Revision of the Ranitomeya fantastica species complex with description of two new species from Central Peru (Anura: Dendrobatidae) - Brown, Jason L.; Twomey, Evan; Pepper, Mark; Rodriguez, Manuel Sanchez (Zootaxa, 2008)
We describe two new species of poison frogs (genus Ranitomeya) from the central Rio Huallaga drainage and adjacent Cordillera Azul in central Peru. Both species were previously considered to be members of Ranitomeya fantastica, a species described from the town of Yurimaguas, Peru. Extensive sampling of putative R. fantastica (including near-topotypic material) throughout central Peru, and the resulting morphological and phylogenetic analysis has led us to conclude that R. fantastica sensu lato is a complex of three closely related species rather than a single, widely distributed species. The first of these species occurs near the type locality of R. fantastica but bears significant dissimilarity to the original type series and forms a monophyletic clade that is distributed throughout an expansive lowland zone between Rio Huallaga and Rio Ucayali. This species is diagnosable by its brilliant red head and advertisement call differences. The second new species has long been considered a color morph of R. fantastica, although our analysis shows that it is genetically distinct from even adjacent populations of R. fantastica. This species is restricted to the Huallaga Canyon near Chazuta and is primarily diagnosed on the basis of nucleotide sequences, although it does possess additional morphological and vocal characteristics which are distinct from R. fantastica.